(untitled) (Journal of Medical Sciences, 2023)
Aim: To determine if primary and preparatory school textbooks in Libya adequately provided knowledge relevant to oral health education. Method: Content analysis of all primary and preparatory school textbooks in Libya based on relevance to oral health education. Any text, picture or illustration, exercise related to oral health was collected and categorized in frequency tables and then percentages were calculated from each table. Results: In general, 21 text books (33%) of 64 textbooks contained items about oral health education. 78 items were found related to oral health information in textbooks of several school subjects. Majority of items were presented as pictures and illustrations (44%) and concentrated in Arabic languages subject (69%). largest percentage of items was about personal care of the teeth and gums (50%) and little information were related to oral diseases, sugar & dental health, relation of diet to oral health, role of fluoride in caries prevention and impact of smoking on oral health. Conclusion: The primary and preparatory school curricula in Libya do not adequately address oral health education, and this study brought attention to the need for further curriculum revision by experts in the ministry of education and the center of educational curricula & research in order to either develop school curricula that adequately incorporate oral health education or add oral health education as a separate subject to existing school curricula.